Wage inequality and overeducation in a model with efficiency wages - Peter Skott (University of Massachusetts, Department of Economics, 2005)
This paper shows that the existence and persistence of overeducation can be explained by an extension of the efficiency wage model. When calibrated to fit the amounts of overeducation found in most empirical studies, the model implies that both the relative wage and the relative employment rate of high-skill workers depend inversely on aggregate economic activity. Keeping aggregate employment constant, furthermore, low-skill unemployment rises following an increase in the relative supply of high-skill labor, and relative wages may be insensitive to changes in relative labor supplies. The model may help explain rising wage inequality in some countries since the early 1970s. JEL Categories: J31
Keywords: 330; Wage inequality; overeducation; efficiency wages